How elite athletes with a spinal cord injury sweat during exercise - An exploratory study - Hertig-Godeschalk, A.; Perret, C. (Sports, 2024)
Background: Sweat and thermal responses in individuals with spinal cord injury (SCI) are impaired depending on lesion characteristics. This is particularly problematic for athletes and may ultimately lead to reduced performance. This exploratory study investigated the feasibility of field-usable methods to objectively collect data relevant to sweat response in elite athletes with SCI. Differences in sweat response were also evaluated for different athlete characteristics.